Quality Characteristic of Arsik and Boiled Carp (Cyprinus carp) - Tamba, Putri Geovany; Syahrul, Syahrul; Sari, N. Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACKThe aims ofthis study to understand the characteristic qualityof fish wwere cooked with Arsik and boiled Cyprinus carpio. Parameter measured were organoleptic test which keeped in two days. With a good characteristics quality as good as at the first day. At the first day, the aroma good and fresh, the fish in a good condition, the color is yellow and there were not mucus at the fish body. But, the boiled carpcan only stand for one days with good charakteristic quality, aroma good and fresh, the fish in a good condition, and the color is pale yellow. Keywords : carper fish, arsik, organoleptic